The grouchy ladybug - Carle, Eric. (New York : Scholastic, 1977)
A grouchy ladybug, looking for a fight, challenges everyone she meets regardless of their size or strength.
Keywords: Infants, Toddlers or Kindergarten; Ladybugs; Behavior